THE USE OF BERLITZ METHOD TO IMPROVE STUDENTS’ VOCABULARY IN DESCRIPTIVE TEXT - Musliyadi; Qalbi, Nur; Yulianti Natsir, Ratu (FKIP Unismuh Makassar, 2023)
The objective of this research is find out whether Berlitz Method improve students’ vocabulary in English Learning Vocabulary or not. The researcher applied Classroom Action Research (CAR). The sample of the research was the Seventh Grade of SMP Pesantren Guppi Samata Gowa and take class VII A with a research sample of 20 students.The results showed that the students of class VII A at SMP Pesantren Guppi Samata experienced an increase from cycle I to cycle II. Improved vocabulary comprehension through the Berlitz Method This indicates a significant increase in students' reading comprehension from the diagnostic test to cycle I and cycle II, where the average score on the diagnostic test was 42.75. cycle I get the average value to 68.25. There was also a significant increase from cycle I to cycle II where the average student in cycle II was 84.25. From these findings, the researcher concludes that the use of the Berlitz method can improve students' vocabulary skills and make students active in the learning process